How to Be a Man Differently: The intersection of Gender and Disability in the Life Course of a Powerchair Athlete. (October 2022) - Paccaud, Laurent; Marcellini, Anne
This article focuses on the intersection of gender, dis/ability and other social forces in the life course of a young man who has had physical impairments from an early age. Drawing on interactionist theories and applying an ethnographic approach, we analyze the life experiences taking place in multiple social spheres throughout the life phases of Simon, a Swiss powerchair hockey player with cerebral palsy. During his childhood and adolescence, Simon was not in a position to embody the familial ways of performing hegemonic masculinity, and he was functionally dependent on women. Through his ongoing transition to adulthood, his commitment to sport and the process of technologizing his body enabled him to do gender differently and emancipate himself from the familial masculine figure, while remaining reliant on the care provided by women. Thus, we show how the body, context, and life phases contribute to the performances of gender and dis/ability.